Theileria infections in small ruminants in the east and southeast Anatolia. - Altay, Kürşat; Aktaş, Münir; Dumanli, Nazir (My University, 2007)
This study was carried out to determine the prevalence of Theileria (T.) ovis and to investigate the presence of T. lestoquardi in small ruminants by microscopic examination (ME) and polymerase chain reaction (PCR) in the East and Southeast Anatolia. Whole blood samples (677 sheep and 142 goats) and thin blood smears (656 sheep and 139 goats) were collected from Malatya, Muş, Erzincan, Erzurum, I?dir, Diyarbakir and Mardin. Piroplasms of Theileria spp. were detected in 18.29% (120/656) of sheep and 2.88% (4/139) of goats by ME. T. ovis was detected in 58.79% (398/677) of sheep and 11.27% (16/142) of goats by PCR whereas T. lestoquardi was not detected in the same animals.
Keywords: Animals; DNA, Protozoan; Goat Diseases; Goats; Parasitemia; Pilot Projects; Polymerase Chain Reaction; Prevalence; Sheep; Sheep Diseases; Theileria; Theileriasis; Turkey; protozoal DNA; animal; animal disease; article; blood; genetics; goat; goat disease; isolation and purification; parasitemia; parasitology; pilot study; polymerase chain reaction; prevalence; sheep; sheep disease; Theileria; theileriosis; Turkey (republic)